Nefazodone versus sertraline in treatment of posttraumatic stress disorder - (:unkn) unknown (My University, 2002)
Objective: Nefazadone is an antidepressant that have a dual effect on serotonergic transmission by acting as both a reuptake inhibitor presynaptically and an antagonist at 5-HT2A receptor postsynaptically. Some authors have suggested that the 5-HT2A receptor may be involved in the pathophysiology of posttraumatic stress disorder (PTSD). In this study, the efficacy of nefazodone in treatment of PTSD was investigated in comparison to the efficacy of sertraline. Methods: Subjects were randomly assigned to two treatment groups, nefazodone or sertraline group. Sixty subjects were recruited with 30 subjects in each treatment group. PTSD patients were diagnosed by using the Structured Clinical Interview for DSM-IV (SCID-1) and nonstructured psychiatric interview. Measurements have been made every month for a five-months period with six assessment points including the baseline. Primary outcome measures consisted of the Posttraumatic Stress Diagnostic Scale (PDS), the eight-item Treatment-outcome Posttraumatic Stress Disorder Scale (TOP-8), Clinical Global Impression Scale (CGI) ratings. Results: The subjects in both of these groups had significantly improved. There were significant differences between initial and endpoint TOP-8 and CGI scores (p<0.001). Conclusions: The results of the current study suggests that nefazodone is significantly effective as sertraline in treatment of PTSD.
Keywords: Nefazodone; Pharmacotherapy; Posttraumatic stress disorder; Sertraline